2018
DOI: 10.1039/c8fd00087e
|View full text |Cite|
|
Sign up to set email alerts
|

Does cage quantum delocalisation influence the translation–rotational bound states of molecular hydrogen in clathrate hydrate?

Abstract: In this study, we examine the effect of a flexible description of the clathrate hydrate framework on the translation-rotation (TR) eigenstates of guest molecules such as molecular hydrogen. Traditionally, the water cage structure is assumed to be rigid, thus ignoring the quantum nature of hydrogen nuclei in the water framework. However, it has been shown that protons in a water molecule possess a marked delocalised character in many situations, ranging from water clusters to proton transfer in the bulk. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 41 publications
(43 reference statements)
3
36
0
Order By: Relevance
“…Allowing for the nonrigidity of the lattice, not considered in the Devonshire cell model, 112 introduces two effects changing the quantum treatment of these systems: (a) the host-guest (molecule-crystal) interaction energy is minimized by the relaxation of the lattice, and (b) the orientation-dependent lattice relaxations, through coupling of the guest rotations with pseudorotation of the host, induce a significant change, in fact a decrease of the effective rotational constants. Recently, quantum studies 113 of molecules trapped in cages 113,114 found renewed interest, especially with regard to the joint treatment of translation-rotation states. Answering the question whether these systems are quasistructural or not would require detailed experimental high-resolution spectroscopic studies and variational rovibrational treatments, both hindered by the size of some of these systems.…”
Section: Pseudorotationmentioning
confidence: 99%
“…Allowing for the nonrigidity of the lattice, not considered in the Devonshire cell model, 112 introduces two effects changing the quantum treatment of these systems: (a) the host-guest (molecule-crystal) interaction energy is minimized by the relaxation of the lattice, and (b) the orientation-dependent lattice relaxations, through coupling of the guest rotations with pseudorotation of the host, induce a significant change, in fact a decrease of the effective rotational constants. Recently, quantum studies 113 of molecules trapped in cages 113,114 found renewed interest, especially with regard to the joint treatment of translation-rotation states. Answering the question whether these systems are quasistructural or not would require detailed experimental high-resolution spectroscopic studies and variational rovibrational treatments, both hindered by the size of some of these systems.…”
Section: Pseudorotationmentioning
confidence: 99%
“…[22][23][24] In all these calculations, the hydrogen-bonded clathrate hydrate framework was treated as rigid. In a recent study, 25 this constraint was relaxed partially, by performing quantum 5D calculations of the TR levels of H 2 in the small sII hydrate cage, while taking into account the quantum delocalization of the proton nuclei of the framework water molecules arising from their hindered rotations about the fixed positions of their O atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In all these calculations, both the H 2 molecules and the hydrogen-bonded clathrate hydrate framework were treated as rigid. Recently, 30 this constraint was relaxed partially, by performing quantum 5D calculations of the TR levels of (rigid) H 2 in the small sII hydrate cage, while taking into account the quantum delocalization of the proton nuclei of the framework water molecules arising from their hindered rotations about the fixed positions of their O atoms.…”
Section: Introductionmentioning
confidence: 99%